PENGARUH KOMPENSASI DAN JOB INSECURITY TERHADAP INTENSI TURNOVER KARYAWAN PADA PT UNITED SINDO PERKASA KOTA BATAM: Asron Saputra (1-14) - Jurnal Akuntansi Barelang (JURNAL AKUNTANSI BARELANG, 2017)
Human resource is one of important sources in organization or company. One way of managing human resources is to avoid employees turnover intention. This research aims to determine impact of compensation and job insecurity on turnover intention. The research carry out at PT United Sindo Perkasa with total sample 105 employees. The method used on this research is multiple linear regression with statistical package for the social sciences (SPSS) version 21 for statistical processing. Result of this research show that impact of compensation on turnover intention is negative and significant with t-test value -2,437, at the same time impact of job insecurity on turnover intention is positive and significant with t-test value 16,390. from this research can be discovered that impact of compensation and job insecurity on turnover intention is 79,8 percent. While the remaining 20,2 percent is determined by other factor not enlisted in this research.